2008
DOI: 10.1134/s1075701508020037
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature hydrothermal deposits in the rift zone of the Mid-Atlantic Ridge

Abstract: New data on the low-temperature hydrothermal deposits of the Snake Pit, TAG, Broken Spur, and Lucky Strike fields in the rift valley of the Mid-Atlantic Ridge (MAR) obtained during the 47th cruise of the R/V Akademik Mstislav Keldysh are reported. These deposits are related to focused and diffuse flows of hydrothermal solutions and the material precipitated from hydrothermal plumes. Electron microscopy study allowed us to identify protoferrihydrite, ferrihydrite, goethite, hematite, Mn-feroxyhyte, and Fe-verna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The relatively well-preserved shape of the akaganéite grains compared to the severely altered aspect of the detrital iron oxides (magnetite, ilmenite) contained in the same samples argue for aeolian transportation 14 . On Earth, akaganéite has been described in a limited number of natural settings: (i) as a corrosion product of steel in chloride containing environments or chloride-bearing excavated archaeological iron 28 ; (ii) as a corrosion product of meteorites 29 ; (iii) together with jarosite in lesser amounts, as a natural precipitate from oxidation of iron sulphide minerals during the occasional drying of acidic (pH ~ 2) and chlorinated wetlands, such as the Bottle Bend Lagoon in Australia 30 - note that saline and acidic Lake Orr and Lake Whurr from Western Australia only contain jarosite, likely because of insufficient salinity (hence insufficient Cl content) 31 ; (iv) as a precipitate associated with volcanic hydrothermal fluids or fumaroles 32 – 34 on land; and (v) as a rare mineral in sulfide mounds and chimneys related to oceanic ridge hydrothermalism 35 .…”
Section: Discussionmentioning
confidence: 99%
“…The relatively well-preserved shape of the akaganéite grains compared to the severely altered aspect of the detrital iron oxides (magnetite, ilmenite) contained in the same samples argue for aeolian transportation 14 . On Earth, akaganéite has been described in a limited number of natural settings: (i) as a corrosion product of steel in chloride containing environments or chloride-bearing excavated archaeological iron 28 ; (ii) as a corrosion product of meteorites 29 ; (iii) together with jarosite in lesser amounts, as a natural precipitate from oxidation of iron sulphide minerals during the occasional drying of acidic (pH ~ 2) and chlorinated wetlands, such as the Bottle Bend Lagoon in Australia 30 - note that saline and acidic Lake Orr and Lake Whurr from Western Australia only contain jarosite, likely because of insufficient salinity (hence insufficient Cl content) 31 ; (iv) as a precipitate associated with volcanic hydrothermal fluids or fumaroles 32 – 34 on land; and (v) as a rare mineral in sulfide mounds and chimneys related to oceanic ridge hydrothermalism 35 .…”
Section: Discussionmentioning
confidence: 99%
“…This link is supported by some indirect evidence. The enrichment in Au (0.81-16.52 ppm Au) is identified for the low-T Fe-Mn crusts and films on the surface of sulfide samples of the Snake Pit and Broken Spur hydrothermal fields, MAR [59]. These Fe-Mn crusts also contain detectable amounts of Ti (0.10-0.26 wt % [59]).…”
Section: Chalcopyrite Station 240mentioning
confidence: 94%
“…The enrichment in Au (0.81-16.52 ppm Au) is identified for the low-T Fe-Mn crusts and films on the surface of sulfide samples of the Snake Pit and Broken Spur hydrothermal fields, MAR [59]. These Fe-Mn crusts also contain detectable amounts of Ti (0.10-0.26 wt % [59]). The bulk analyses of sulfides from Axial Seamount show the significant Au-Mn correlation (r = 0.60), and it was suggested that Mn-coatings on fossil chimneys from many of the deposits account for the high Mn associated with some gold-rich samples [60].…”
Section: Chalcopyrite Station 240mentioning
confidence: 94%
“…This process results in local formation of Fe-Mn crusts on rocks free of living mollusks. Such a situation has been described in the Logachev hydrothermal field, where the crew of a Mir manned submersible observed a thick carpet of mollusks around the active Irina-2 hydrothermal mound (Bogdanov et al, 2004). Although a fragment of the Mn crust that was taken nearby was referred to a hydrothermal Mn source, in my opinion, this is a typical hydrogenic deposit.…”
Section: Introductionmentioning
confidence: 93%